2001
DOI: 10.2460/javma.2001.219.805
|View full text |Cite
|
Sign up to set email alerts
|

Multilocation trial of ceftiofur for treatment of postpartum cows with fever

Abstract: Parenteral administration of ceftiofur significantly improved cure rate, milk yield, and rectal temperature in postpartum cows with fever and vaginal discharge or dystocia. These findings provide information to determine appropriate treatment for postpartum cows, which for years has been debated in the dairy industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 10 publications
(10 reference statements)
0
39
0
Order By: Relevance
“…At present systemic treatment using ceftiofur is preferable for the treatment of puerperal metritis (Drillich et al, 2001(Drillich et al, , 2003Zhou et al, 2001;Risco and Hernandez, 2003;Chenault et al, 2004). Nevertheless, comparable cure rates and reproductive performances were found in cows with puerperal metritis treated with ceftiofur compared to affected cows treated by the intrauterine administration of ampicillin or ampicillin with oxacillin (Beetz, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present systemic treatment using ceftiofur is preferable for the treatment of puerperal metritis (Drillich et al, 2001(Drillich et al, , 2003Zhou et al, 2001;Risco and Hernandez, 2003;Chenault et al, 2004). Nevertheless, comparable cure rates and reproductive performances were found in cows with puerperal metritis treated with ceftiofur compared to affected cows treated by the intrauterine administration of ampicillin or ampicillin with oxacillin (Beetz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…But the effects of different diagnostic and therapeutic procedures on reproductive performance have not been unified. Data showed a positive effect (Montes and Pugh, 1993;Smith et al, 1998;Zhou et al, 2001) or no effect or in some cases negative effects (Paisley et al, 1986;Gilbert, 1992;Whitacre, 1992;Olson, 1996;Drillich et al, 2002).…”
mentioning
confidence: 98%
“…22 The effect of ceftiofur on postpartum inflammation and fever has also been assessed and it was found that systemic administration significantly improved cure rate, milk yield, and rectal temperature in postpartum dairy cows with fever and vaginal discharge or dystocia. 15 This article critically evaluates the evidence for treatment of metritis with ceftiofur. The primary criteria for inclusion in the review was based on the current definition of metritis by Sheldon and colleagues 8 and all studies had to use ceftiofur for the treatment of clinical metritis.…”
Section: Discussionmentioning
confidence: 99%
“…22 Administration of ceftiofur to cows with evidence of postpartum fever and uterine discharge showed significant improvement in cure rates, milk yield, and rectal temperature. 15 Although there is evidence to support the use of ceftiofur, the lack of a uniform clinical definition and the diversity in types and dosages of ceftiofur used has made interpretation of current research difficult. This article uses an evidence-based approach to summarize the current evidence for the use of ceftiofur as the treatment of metritis.…”
Section: Pharmacologic Treatment Options Antibiotic Therapymentioning
confidence: 98%
See 1 more Smart Citation